Supergroup F Wolbachia with extremely reduced genome: transition to obligate insect symbionts - Mahmood, Sazzad; Nováková, Eva; Martinů, Jana; Sychra, Oldřich; Hypša, Václav (Microbiome, 2023)
BACKGROUND: Wolbachia belong to highly abundant bacteria which are frequently found in invertebrate microbiomes and manifest by a broad spectrum of lifestyles from parasitism to mutualism. Wolbachia supergroup F is a particularly interesting clade as it gave rise to symbionts of both arthropods and nematodes, and some of its members are obligate mutualists. Investigations on evolutionary transitions among the different symbiotic stages have been hampered by a lack of the known diversity and genomic data for the supergroup F members. RESULTS: Based on amplicon screening, short- and long-read WGS approaches, and laser confocal microscopy, we characterize five new supergroup F Wolbachia strains from four chewing lice species. These strains reached different evolutionary stages and represent two remarkably different types of symbiont genomes. Three of the genomes resemble other known members of Wolbachia F supergroup, while the other two show typical signs of ongoing gene inactivation and removal (genome size, coding density, low number of pseudogenes). Particularly, wMeur1, a symbiont fixed in microbiomes of Menacanthus eurysternus across four continents, possesses a highly reduced genome of 733,850 bp. The horizontally acquired capacity for pantothenate synthesis and localization in specialized bacteriocytes suggest its obligate nutritional role. CONCLUSIONS: The genome of wMeur1 strain, from the M. eurysternus microbiome, represents the smallest currently known Wolbachia genome and the first example of Wolbachia which has completed genomic streamlining as known from the typical obligate symbionts. This points out that despite the large amount and great diversity of the known Wolbachia strains, evolutionary potential of these bacteria still remains underexplored. The diversity of the four chewing lice microbiomes indicates that this vast parasitic group may provide suitable models for further investigations. Video Abstract.
Keywords: Insecta; Symbiosis; Biological Evolution; Nematoda; hlístice; Animals; Wolbachia; hmyz; symbióza; Phylogeny; zvířata; fylogeneze; biologická evoluce